The Pancasila and Citizenship Education Model as a Constitutional Education in Elementary/Islamic Elementary Schools - Mulyani, Heny; Sapriya, Sapriya; Hubi, Zindan Baynal; Insani, Nisrina Nurul; Nurgiansah, T Heru (Al-Aulad: Journal of Islamic Primary Education, 2024)
The purpose of this research is to investigate the role of Pancasila and Civic Education (PPKn) in enhancing constitutional awareness among students at the elementary school/madrasah ibtidaiyah level, and to elucidate effective teaching methods to achieve this goal. The research methodology employed is literature review method, analyzing various relevant literature pertaining to the research topic. The important findings of this research are that cooperative learning models such as Numbered Heads Together and Think Pair Share can be used to improve students' understanding and learning outcomes in Civics. In addition, interactive learning models such as Role Playing, Broken Triangle, Square and Heart, and digital citizenship can also increase constitutional awareness among students. Teachers play a significant role in implementing Civics and cultivating constitutional awareness in each student, with the purpose of making Civics implementation in elementary schools/madrasah ibtidaiyah an effort to shape individuals in Indonesia who possess strong personalities and a sense of responsibility towards their country. By using effective learning methods, Civics can be an important instrument in building constitutional awareness and student character.